Remote monitoring and control system of a water distribution network using LoRaWAN technology - Yauri Rodríguez, Ricardo (2023)
The problems related to the proper management and control in the distribution of potable water affect environmental sustainability generated by leaks and breaks in the infrastructure, causing leaks and loss of water. According to reports from the National Superintendence of Sanitation Services of Peru, more than 50% of complaints about the water service are related to billing problems and water leaks. It is for this reason that technologies such as the Internet of Things technology contribute to generating solutions for the automatic acquisition of data in residences and houses. That is why this paper aims to use long-range and low-power wireless communication systems to improve the service-oriented to the control of the water distribution network, monitoring of vandalism, and detection of anomalous events, reducing response time and economic losses. The paper's development methodology considers the implementation of a water controller node with flow control sensors and solenoid valves and a gateway with Lora communication. In addition, a solenoid valve control circuit and a remote visualization and control system are implemented. The results indicate that the implemented nodes allow adequate monitoring and control in real-time of the water flow, contributing to the adequate management of its consumption and supporting the detection of anomalous events using a Web application.